Experimental investigation into ultrafast laser ablation of polypropylene by burst and single pulse modes. (August 2022) - Molinuevo, J.; Rodríguez-Vidal, E.; Quintana, I.; Morales, M.; Molpeceres, C.
Graphical abstract: Highlights: Single Pulse (SP) and burst mode ablation in femtosecond range have been explored. A single pulse cannot generate any crater, but a swelling phenomenon is observed. The advantages of using burst pulses over SP have been proven. The SP remove higher volume, but its removal rate is lower than the burst mode. Abstract: Experimental investigation into ultrashort laser ablation by burst and Single Pulse (SP) modes on Polypropylene was performed. Isolated craters with different set of laser parameters were produced on flat polymer samples to assess the influence of the temporal separation between pulses on surface quality, removal rate (time needed to remove a certain volume) and ablation efficiency (pulse energy needed to remove a certain volume). The laser parameters that allow the development of structures with minimum redeposited material splashed around them and maximum removal rates were identified. Pulse energies of 2.5 μJ and 6 μJ were identified as the removal pulse energy threshold and the value from which a structure depth saturation starts, respectively. The use of bursts provides improved quality and higher removal rates compared to the Single Pulse mode when the same number of pulses of identical pulse energies were emitted in both cases, even though the total eliminated volume is higher in the SP mode. The advantages of using bursts of 3 pulses are reported. Increasing the number of pulses per burst to 4 do not increase the removal rate when compared to bursts of 3 pulses.